The value of earning for learning: Performance bonuses in immigrant language training - Olof Aslund; Mattias Engdahl (Institute for the Study of Labor (IZA), 2012)
We study the effects of performance bonuses in immigrant language training for adults. A Swedish policy pilot conducted in 2009-2010 gave a randomly assigned group of municipalities the right to grant substantial cash bonuses to recently arrived migrants. The results suggest substantial effects on average student achievement. But these were fully driven by metropolitan areas; in other parts of Sweden performance was unaffected. The relative effects were larger for younger students but similar for men and women, and present for migrants from different parts of the world. The bonus had a less clear impact on enrollment, but there are indications that it may have increased the probability of progressing to bonus-awarding courses in metropolitan areas.
Keywords: J08; J15; I24; 330; immigration; language training; performance bonus; Migranten; Sprache; Lernen; Leistungsentgelt; Subvention; Soziale Integration; Schweden